Graffiti, Street Art and Murals in the Age of the Neoliberal City: The Muralization of Capital - Abram, Sandi (SAUC - Street Art and Urban Creativity (repository), 2024)
The article explores graffiti, street art, and murals in the context of the neoliberal city, highlighting the transformation of these forms in the context of growing urban commodification, touristification and gentrification. The paper shows how contemporary neoliberal urbanism has driven the concept of the creative city that, in the framework of late-capitalist inter-urban rivalry, recuperated graffiti, street art and murals. Drawing on the growing body of literature in the field of graffiti and street art studies, and combining it with urban anthropology, the analysis of ethnographic material collected in Ljubljana (Slovenia) illuminates the role of graffiti and contemporary street art in the context of the neoliberal city – both as anti-gentrification politics and pro-gentrification policies. The paper argues for a nuanced understanding of the role of graffiti, street art and murals under the neoliberal regime of urban development, emphasizing the multi-layered nature of graffiti and street art: as a form of political activism, as an object of commodification, and as an instrument for de-ideologization, or what the author calls the muralization of capital.